2020
DOI: 10.1002/iid3.307
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory infections regulated blood cells IFN‐β‐PD‐L1 pathway in pediatric asthma

Abstract: Background: Respiratory infections, in general, and rhinovirus infection specifically are the main reason for asthma exacerbation in children and programmed cell death protein 1 ligand (PD-L1) expression inhibits T cell responses. Objective: Could the interferon (IFN) type I expression in peripheral blood mononuclear cells (PBMCs) improve disease exacerbation in pediatric asthma? Results: Here we found increased level of PD-L1 messenger RNA (mRNA) in total blood cells isolated from preschool children with viru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…In the same cohort was found that the released levels of IFN-b from PBMCs were associated with an induction of PD-L1, however only in the control group (112). In the asthma group, the asthmatic patients with higher IFN-ß level have less PD-L1 expression in total blood cells and better lung function (112). This finding suggests that IFN-ß suppresses PD-L1 expression in asthma, and the improvement of IFN type I expression in PBMCs in pediatric asthma may ameliorate asthma exacerbation.…”
Section: Pd-l1mentioning
confidence: 84%
See 1 more Smart Citation
“…In the same cohort was found that the released levels of IFN-b from PBMCs were associated with an induction of PD-L1, however only in the control group (112). In the asthma group, the asthmatic patients with higher IFN-ß level have less PD-L1 expression in total blood cells and better lung function (112). This finding suggests that IFN-ß suppresses PD-L1 expression in asthma, and the improvement of IFN type I expression in PBMCs in pediatric asthma may ameliorate asthma exacerbation.…”
Section: Pd-l1mentioning
confidence: 84%
“…In a human cohort study, it was recently described that preschoolers suffering from rhinovirus-induces asthma and with reduced forced expiratory volume in 1 second (FEV1) and high serum levels of C-reactive protein (CRP) show increased level of PD-L1 mRNA in total blood cells. In the same cohort was found that the released levels of IFN-b from PBMCs were associated with an induction of PD-L1, however only in the control group (112). In the asthma group, the asthmatic patients with higher IFN-ß level have less PD-L1 expression in total blood cells and better lung function (112).…”
Section: Pd-l1mentioning
confidence: 94%
“…A short cohort study showed that in the control group, the IFN released by PBMC was related to the production of PD-L1. Yet, the study also showed that higher IFN-β levels were associated with the lower level of PD-L1 and better lung function ( 87 ). To summarize, PD-L1 might be a pro-inflammatory cytokine in RV-related asthmatics.…”
Section: Cytokines Produced In Rv-induced Immunoreactionsmentioning
confidence: 99%
“…The human tissue explant model of viral infection maintains tissue-architecture during the infection process, including the presence of multiple inflammatory cell types, allowing the effect of asthma and viral infection to be compared in multiple resident cell types simultaneously. This model has been demonstrated to reflect human in-vivo viral tropism, influenza virus T cell epitope presentation, and inflammatory mediator release patterns more effectively than in-vitro cell systems, and we have previously demonstrated using lung parenchyma explants that PD-L1 expression patterns post-influenza infection are modulated in chronic obstructive pulmonary disease (5,9) Studies by others have suggested abnormal expression of the PD-1 pathway in atopic individuals and allergic asthma (10,11) but have not established whether anti-PD-1 therapy could be useful or detrimental in the treatment of allergic asthmatics in the context of acute viral exposure.…”
Section: Introductionmentioning
confidence: 99%
“…Studies by others have suggested abnormal expression of the PD-1 pathway in atopic individuals and allergic asthma ( 10 , 11 ) but have not established whether anti-PD-1 therapy could be useful or detrimental in the treatment of allergic asthmatics in the context of acute viral exposure.…”
Section: Introductionmentioning
confidence: 99%